Analysis of Leachate Water Distribution in Bakung Final Waste Disposal Location (TPA) Using Resistance Geoelectric Methods in Keteguhan Permai Housing Bandar Lampung - Alicya Inmas Mauladika (Ridwan Institute, 2022)
Poor waste management is one of the most frequent environmental problems in Indonesia. We know that the waste generated as a result of daily human activities will be transported, then disposed of at the Final Disposal Site (TPA). The lack of attention to WWTP maintenance at the Daffodil TPA can be seen from the thickness of the sediment at the WWTP dam. The thickness of the sediment in the WWTP causes leachate from the TPA not to fully enter the WWTP but flows directly into the river and seeps into the ground. Thus, this research was conducted as an aim to explain the spread of leachate pollution in shallow groundwater in the Keteguhan Permai housing complex. The method is quantitative. The results of this study indicate that groundwater is shallow in the study area, namely, Keteguhan Permai housing has been polluted by leachate. The average leachate intrusion depth in this study area is less than 13 meters with a resistivity value of less than 10?m.